The three layerings of Malay Aristocratic ornamentations: survival of semantic categories amidst stylistic changes - Ali, Maisarah; Jahn Kassim, Puteri Shireen; Samsudin, Abu Dzar; Raja Abdul Kadir, Tengku Anis Qarihah (2019)
Public architecture in the Malay world refer to the relationships between the palaces and mosques and the changes highlight the evolution and the complexity of life brought about by Colonial-led modern changes starting from 18th centuries, spaces in these Malay palaces and Aristocrats homes or the public realm, had become more complex and thus their semantic identification and naming of elements have not been adequately addressed. The research will focus on the Malay Palace and aristocratic house and highlights on its ornamentation influence towards their colonial ruler. The ornamentation includes extended variations of the "larik", "papan ukir", "jerejak" and "kekisi". The paper maps the influence of external forces such as Colonisation on regional architecture and that time and suggests three substreams of stylistic development in Classical Malay architecture.